2001
DOI: 10.1136/bjsm.35.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic characteristics of male athletes of different age

Abstract: Two dimensionally guided M mode and Doppler echocardiographic data for 578 male subjects (106 non-athletic and 472 athletes) were analysed from two aspects: (a) in the young adult category (19-30 years of age), competitors in diVerent groups of sports were studied; (b) in the diVerent age groups (children, 10-14 years; adolescent juniors, 15-18 years; young adults, 19-30 years; adults, 31-44 years; older adults 45-60 years), data for athletes and non-athletes were compared. Morphological variables were related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
43
0
12

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 35 publications
16
43
0
12
Order By: Relevance
“…As a relative parameter, the quotient LV end-diastolic WT/ID was also calculated. On the basis of our 15,26 and other previous studies, 27,28 the following exponent-corrected indices were used to relate cardiac measures to body size:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a relative parameter, the quotient LV end-diastolic WT/ID was also calculated. On the basis of our 15,26 and other previous studies, 27,28 the following exponent-corrected indices were used to relate cardiac measures to body size:…”
Section: Methodsmentioning
confidence: 99%
“…In older people, it is more difficult to assess the role of hypertrophy. Based on sports cardiologic studies 15,[19][20][21][22][23][24] made in the last few years, the two types of hypertrophy can be best separated functionally, primarily by using the parameters of diastolic function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This point has been controversial in other rodent models with some studies showing LV dilation with aging cardiomyopathy in rodents (Iemitsu et al 2002;Luptak et al 2007;Niemann et al 2010;Boyle et al 2011), whereas others did not (Afilalo et al 2007). Importantly, the majority of (Gardin et al 1979;Rodeheffer et al 1984;Pavlik et al 2001). However, CR reduced LVEDD and LVESD significantly.…”
mentioning
confidence: 99%
“…The study on the long term and short-term effects of heavy dynamic exercise on neural control of heart rate may explain the coexistence of training bradycardia, with signs of enhanced sympathetic activity in trained champion athletes (Furlan et al, 1993). E/A quotient (ratio of peak velocity during early and late diastole) suggested that regular physical activity at an older age might protect against age dependent impairment of diastolic function (Pavlik et al, 2001). In the study of the effects of aekivanjima.…”
Section: Tonći Grgurinović Et Al: Differences In Health Indicators mentioning
confidence: 99%